Horizontal seed dispersion patterns of Californian thistle (Cirsium arvense) - Wallace, I.A.; Eerens, J.PJ.; Rahman, A.; Clarkson, B.D. (New Zealand Plant Protection, 2005)
Few Californian thistle seeds find their way to the soil seed bank raising a question about their dispersal and fate The horizontal seed distributions around ten Californian thistle patches were studied on two farms Thirteen seed traps were placed on the ground in four directions around each patch seven of these were downwind (prevailing wind direction) at different distances from the patches Seed traps were left for 48 h and trapping was repeated three times The highest numbers of seeds were collected at the edge of a patch with numbers declining exponentially as distance from the patch increased The horizontal seed distribution was significantly affected by landscape type and/or landscape objects Relatively more seeds were captured away from a patch that had trees growing a short distance upwind than from patches on flat land A similar pattern of disturbance was observed for patches located in a gully